Incorporating sensor measurements using data assimilation and machine learning to improve the accuracy of thermal finite element models - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2023)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2022.